Brand loyalty towards fashion hijab industry / Anna Shaffera Muhammad Khairil - Muhammad Khairil, Anna Shaffera (2020)
The goal of the present study was to analyze the brand loyalty of customers by considering the position of perceived value, perceived quality, brand satisfaction and commitment to the relationship. A field survey was conducted to collect data from the respondent in the region of Kota Kinabalu as well as to know their honest thoughts about their preferred marks. The model proposed was tested using a structural equation analysis. The result showed that perceived value, perceived quality and brand satisfaction and relationship engagement had a substantial effect on brand loyalty. And brand satisfaction was the most important contributor to building brand loyalty. Therefore, study variables were defined as the mediating role. Overall , the proposed theoretical structure contained an appropriate degree of brand loyalty explanatory capacity. With a lack of research on the buying behavior of the brand hijab customer, the findings can be used meaningfully to improve customer loyalty.